Problems with Improvement of the Structure of Polish Farms - Dzun, Włodzimierz; Józwiak, Wojciech (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2009)
In Polish agriculture progress in the improvement of the structure of farms in accordance with economic quantity is insufficient in relation to the challenge of intensifying competition on the common agricultural market of the European Union and on the world agricultural market. In the conditions of globalisation and integration only modern and economically strong farms can ensure themselves a stable position in the emerging division of labour within EU 27. In the conditions prevailing in Poland the principal factor of improvement in the structure of farms in accordance with economic quantity is a radical change in the acreage structure of farms and mainly an increase in the proportion of farms having 30 ha and over 30 ha of arable land. However, progress in this respect, especially in recent years, has been very slow. The main barrier to faster progress is the lack of supply of arable land coming from farms liquidating or reducing their agricultural production. In this situation the popularisation and consolidation of the institution of lease ought to become an important factor of improvement in the agrarian structure of Polish agriculture. Therefore, the agricultural policy ought to facilitate the operation of farms using land under lease agreements and to strengthen the lessees' conviction about the lasting character of their work on the leased land.
Keywords: structure of farms in accordance with economic quantity; acreage structure of agricultural farms; economic results of agricultural farms; barriers to an improvement in the structure of farms; lease of arable land